Efficient CRISPR/Cas9-mediated editing of trinucleotide repeat expansion in myotonic dystrophy patient-derived iPS and myogenic cells. Issue 16 (27th June 2018) - Dastidar, Sumitava; Ardui, Simon; Singh, Kshitiz; Majumdar, Debanjana; Nair, Nisha; Fu, Yanfang; Reyon, Deepak; Samara, Ermira; Gerli, Mattia F M; Klein, Arnaud F; De Schrijver, Wito; Tipanee, Jaitip; et al.
Abstract: CRISPR/Cas9 is an attractive platform to potentially correct dominant genetic diseases by gene editing with unprecedented precision. In the current proof-of-principle study, we explored the use of CRISPR/Cas9 for gene-editing in myotonic dystrophy type-1 (DM1), an autosomal-dominant muscle disorder, by excising the CTG- repeat expansion in the 3′-untranslated-region ( UTR ) of the human myotonic dystrophy protein kinase ( DMPK ) gene in DM1 patient-specific induced pluripotent stem cells (DM1-iPSC), DM1-iPSC-derived myogenic cells and DM1 patient-specific myoblasts. To eliminate the pathogenic gain-of-function mutant DMPK transcript, we designed a dual guide RNA  based strategy that excises the CTG -repeat expansion with high efficiency, as confirmed by Southern blot and single molecule real-time (SMRT) sequencing. Correction efficiencies up to 90% could be attained in DM1-iPSC as confirmed at the clonal level, following ribonucleoprotein (RNP) transfection of CRISPR/Cas9 components without the need for selective enrichment. Expanded CTG repeat excision resulted in the disappearance of ribonuclear foci, a quintessential cellular phenotype of DM1, in the corrected DM1-iPSC, DM1-iPSC-derived myogenic cells and DM1 myoblasts. Consequently, the normal intracellular localization of the muscleblind-like splicing regulator 1 (MBNL1) was restored, resulting in the normalization of splicing pattern of SERCA1 . This study validates the use of CRISPR/Cas9 for gene editing of repeat expansions.